Design and Manage Integrated Marketing Communication - Hapsawati Taan (Journal of International Conference Proceedings (JICP), 2018)
The role of marketing communication is as a means used by companies in an effort to inform, persuade, and remind consumers direct or indirect about the products and brands that producers sell. Aim from this paper is to find out: (1) The role of marketing communication in the company. (2) The process of designing and developing effective communication. (3) Determining factors in the marketing mix communication. (4) Management of the integrated marketing communication process. Conclusion: Integrated marketing communication contributes to brand equity by building brand in memory (brand awareness) and creating a brand image (brand image) which includes six components namely advertising, sales promotion, event, public relations and publicity, direct marketing, and sales personal. Suggestions: (1) The company should consider several factors in developing the promotion mix for example the type of product market, readiness. (2) Companies should conduct marketing communications not only focusing on overcoming the gap in product awareness, image or preferences in the target market. Keywords: Marketing Communication, Process, Effective